Penetapan Kadar Kuersetin pada Obat Herbal yang Mengandung Ekstrak Tempuyung (Sonchus arvensis) Menggunakan KLT Densitometri - Asih Imulda Hari Purwani; Krisna Kharisma Pertiwi; Dwi Wahyuni; Rachma Nurhayati (Bioscientist : Jurnal Ilmiah Biologi, 2024)
Quercetin are the main marker compounds in extracts of Sonchus arvensis which show nephrolithiasis activity. For quality control of herbal medicines, Densitometric Thin Layer Chromatography (TLC) method has been developed in this study using quercetin as phytochemical markers. Objective: Determination for quercetin in herbal medicines. Determination of quercetin by determining the composition of the mobile phase, the wavelength of the analysis, the saturation time, the elution distance and the volume of the spot. The parameters observed in the optimization method and stability test are area, retardation factor (Rf), peak shape and resolution (Rs). The composition of selected mobile phase which results good separation and symmetrical peak shape is chloroform: methanol: dichloromethane: acetonitrile: formic acid (6: 2: 2: 0.05: 0.05 v/v/v/v/v) with a wavelength of 335 nm, time of saturation is 30 minutes, elution distance is 8 cm, volume of spots is 10 µL and Rf 0.48. In this study, it was shown that there were no factors that had a significant effect so that the method could be applied for the determination of quercetin levels in herbal medicines.The research data showed that the range of levels on quercetin 3.26%.